Role of 'Kisan Call Center', Pune in dissemination of agricultural technology - H.P.Bondale,; A.M. Chavai,; V.J. Tarde,; G.K.Sasane, (Journal of Agricultural Extension Management, 2025)
The challenges before Indian agriculture are immense. This sector needs to grow at a faster rate than in the past to allow for higher per capita income and consumption. It is an accepted fact that sound agricultural development is essential for. Overall economic progress. About two thirds of the workforce are directly or indirectly dependent on agriculture. This sector generates about 28 percent of the GDP and over 15 percent of exports. Rising consumer prosperity and the search by farmers for higher incomes will simultaneously drive crop diversification. Export opportunities for agricultural products are also expected to continue to grow, provided India could meet the stability, quality and presentation standards demanded by foreign trade and consumers and maintain its comparative advantage as a relatively low cost producer